PENGARUH LINGKUNGAN SOSIAL TERHADAP MINAT KEWIRAUSAHAAN REMAJA DI DESA BATULAPPA - Jamil, Jamil; Khaeruddin, Khaeruddin (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, 2021)
This study aims to determine the influence of the social environment on adolescent entrepreneurial interest in Batulappa Village. The data collection techniques in this study are interviews, documentation, and questionnaires. The sample in the study was 32 respondents in the category of teenagers. The data analysis technique in this study used quantitative descriptive analysis. Based on the results of the study, it can be seen that the influence of the social environment on entrepreneurial interest as a whole has a very positive effect.